2022
DOI: 10.18063/ijb.v8i2.528
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Assisted Nephrotoxicity Testing with Bioprinted Renal Spheroids

Abstract: We used arrays of bioprinted renal epithelial cell spheroids for toxicity testing with cisplatin. The concentration dependent cell death rate was determined using a lactate dehydrogenase assay. Bioprinted spheroids showed enhanced sensitivity to the treatment in comparison to monolayers of the same cell type. The measured dose-response curves revealed an inhibitory concentration of the spheroids of IC50 = 9 ± 3 μM in contrast to the monolayers with IC50 = 17 ± 2 μM. Fluorescent labeling of a nephrotoxicity bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The developed CNN model successfully categorized cell viability into three classes with a balanced accuracy of 78.7%. CNN has also demonstrated good generalization performance when predicting the cell viability of bioprinted renal spheroids under varied inhibitory concentrations as well as experimental settings [ 47 ] . This may be a new pathway to prompt efficient cell viability studies by segmenting cell/nuclei in fluorescence images and then counting live/dead cells using the developed DL models.…”
Section: ML Applications In Cell Performance Studiesmentioning
confidence: 99%
“…The developed CNN model successfully categorized cell viability into three classes with a balanced accuracy of 78.7%. CNN has also demonstrated good generalization performance when predicting the cell viability of bioprinted renal spheroids under varied inhibitory concentrations as well as experimental settings [ 47 ] . This may be a new pathway to prompt efficient cell viability studies by segmenting cell/nuclei in fluorescence images and then counting live/dead cells using the developed DL models.…”
Section: ML Applications In Cell Performance Studiesmentioning
confidence: 99%
“…Finally, as can be seen in table 2, ML has been studied to automatically extract relevant features related to the state of bioprinted cells from image data [104,109]. In an interesting application, Yao et al proposed an unsupervised algorithm based on generative adversarial networks (GANs) for the automatic segmentation of cell nuclei in 3D scaffolds (figure 6(a)).…”
Section: For Post-process Qcmentioning
confidence: 99%
“…The team demonstrated that the detection effect of the method was good, providing a new solution for the rapid screening of 3D-bioprinted organs. Tröndle et al [ 92 ] obtained a renal sphere by bioprinting and tested its toxicity based on deep learning technology. Due to the precise deposition of low- volume, low-viscosity bioink, the renal sphere was generated by drop-on-demand bioprinting.…”
Section: Defect Detection During 3d Bioprintingmentioning
confidence: 99%